Mengimplementasi Algoritma Self-Organizing Map untuk pemetaan data kasus COVID-19 di Jawa Barat - Achmad Suharno; Ahmad Faqih; Tati Suprapti (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
ABSTRACT COVID-19 is a contagious disease characterized by respiratory symptoms. This virus has a higher rate of spread or transmission than the previous variant of the virus. The mapping of the area of COVID-19 spread carried out by the government has not been optimally adhered to by the community. High community activity (mobility) is one of the causes of the spread of COVID-19. People are still traveling (mobility) in areas of high COVID-19 spread. The public needs a lot of additional information about mapping the spread of COVID-19. The grouping method uses the Self-Organizing Map algorithm. The dataset used is the latest data that includes the number of closecontact_total (direct interaction), suspect_total (total covid symptoms), probable_total (suspected exposure), confirmation_total (confirmed covid-19) in West Java. Furthermore, the results of the grouping are evaluated. Evaluation in the form of internal evaluation using davies-bouldin indeks. The expected result is mapping of kab / city in West Java based on the latest Covid data with a DBI value of 1.04768 at k = 6 Keywords: Self-Organizing Map, Davies Bouldin Indeks, Covid-19 West Java